Ranajit Guha and Dipesh Chakrabarty on the Limits of History: dialogues with Rabindranath Tagore - Santos Ribeiro de Oliveira, Mirian; Cristovão dos Santos, Pedro Afonso (História da Historiografia: International Journal of Theory and History of Historiography, 2025)
At the turn of the 21st century, South Asian historians Ranajit Guha (1923-2023) and Dipesh Chakrabarty (1948-) turned their attention to the discussion of the limits of history. In this paper, we analyze the limits of history and possible new approaches to historiography as understood by both historians, with a focus on the dialogue with the works by Rabindranath Tagore proposed by them. We argue that: 1) the validity of history as a concept or as discipline to deal with categories such as the Anthropocene or the planet does not depend on expanding the conceptual limits of history indefinitely, and could benefit from the methodological strategy of writing oneself into a history that is, to some extent, one’s own; 2) to do so, creativity, imagination, and empathy combine not to write another version of a single and all-encompassing history, but to recognize multiple worlds that articulate the human, the non-human, and the more-than-human.